2017
DOI: 10.2147/ijnrd.s101808
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in patients with chronic kidney disease: etiology and management

Abstract: Abstract:Patients with chronic kidney disease (CKD), including those with end-stage renal disease, treated with dialysis, or renal transplant recipients have an increased risk for cardiovascular disease (CVD) morbidity and mortality. Dyslipidemia, often present in this patient population, is an important risk factor for CVD development. Specific quantitative and qualitative changes are seen at different stages of renal impairment and are associated with the degree of glomerular filtration rate declining. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
159
3
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(183 citation statements)
references
References 30 publications
6
159
3
15
Order By: Relevance
“…These changes could be observed in the early stages of kidney disease [25,26], and serious kidney dysfunction led to the development of severe dyslipidemia [2,3,27]. In our study, we found a higher LDL-C level in the decreased eGFR group compared to the normal eGFR group.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These changes could be observed in the early stages of kidney disease [25,26], and serious kidney dysfunction led to the development of severe dyslipidemia [2,3,27]. In our study, we found a higher LDL-C level in the decreased eGFR group compared to the normal eGFR group.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies have indicated that patients with kidney disease also exhibit significant alterations in lipid metabolism and that the progression of kidney disease may lead to severe dyslipidemia [2][3][4]. Importantly, it is worth noting that disorders in lipid metabolism can also be observed in patients even in the early stage of kidney dysfunction [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The function and size of the left atrium are influenced by various factors including mitral valve disease, hypertension, obesity, and intrinsic LA disorders and particularly systolic and diastolic functions of LV. With the development of left ventricular diastolic dysfunction, LA is chronically exposed to abnormal filling pressures, which end up with volumetric changes . In our study, IVS increased in both groups as compared to normal healthy population, but the increase in the HD group was more notable and statistically significant, and we implied that the presence of ventricular hypertrophy in HD patients may contribute to left atrial dysfunction due to the above‐mentioned conditions.…”
Section: Discussionmentioning
confidence: 45%
“…function, LA is chronically exposed to abnormal filling pressures, which end up with volumetric changes. 5,[9][10][11][12] In our study, IVS increased in both groups as compared to normal healthy population, but the increase in the HD group was more notable and statistically significant, and we implied that the presence of ventricular hypertrophy in HD patients may contribute to left atrial dysfunction due to the abovementioned conditions.…”
Section: Discussionmentioning
confidence: 62%
“…Future larger studies with an increased sample size would be need to confirm this preliminary study. Our finding of hyperlipidemia in AMR group could be linked to the fact that hyperlipidemia is the most common form of dyslipidemia, a common complication in CKD patients, associated with the decline in kidney function, hypertriglyceridemia, low HDL, and low or normal LDL (34).…”
Section: Discussionmentioning
confidence: 86%